Legal Aspects of The Agreement to Purchase a House Owned by a Bankrupt Debtor - Khairunnisah; Gusti Heliana Safitri; Dina Paramitha Hefni Putri (Faculty of Law, Universitas Pekalongan, 2024)
This study examines the philosophical and legal basis of the sale and purchase agreement of bankrupt objects involving the assets of the debtor who has been declared bankrupt. The transaction is not merely an economic exchange, but must also integrate ethical values ​​of muamalah, such as good faith (husn al-niyyah), distributive justice, and transparency of information in order to minimize the level of uncertainty (gharar) inherent in bankrupt assets Faustina & Hoesin (2022). From an Islamic perspective, the basic sharia principles that guide the validity of the sale and purchase agreement are an important foundation so that the rights of buyers with good faith are maintained and protection of creditor interests is still accommodated through mechanisms such as actio pauliana (Haryanto & Calvin, 2021). Furthermore, this study highlights the problems that arise in legal practice, such as the validity of the sale and purchase agreement (PPJB) that has not been formally certified, which has the potential to complicate legal certainty for buyers and threaten the balance between private and public interests (Amini & Wardani, 2023). By applying a normative legal methodology that relies on secondary data from legal literature and court decisions, this study formulates a transaction mechanism that not only ensures fairness and transparency, but also strengthens the integrity of the legal and economic systems in bankruptcy situations. On the other hand, the integration of ethical values ​​​​and principles of justice is expected to create harmonious cooperation between bankrupt actors, creditors, and good-faith buyers, thereby creating sustainable legal stability and certainty.